Fructose-1,6-bisphosphate aldolase of Neisseria meningitidis binds human plasminogen via its C-terminal lysine residue - Shams, Fariza; Oldfield, Neil J.; Lai, Si Kei; Tunio, Sarfraz Ali; Wooldridge, Karl G.; Turner, David P.J. (Wiley Open Access, 2016)
Neisseria meningitidis is a leading cause of fatal sepsis and meningitis worldwide. As for commensal species of human neisseriae, N. meningitidis inhabits the human nasopharynx and asymptomatic colonization is ubiquitous. Only rarely does the organism invade and survive in the bloodstream leading to disease. Moonlighting proteins perform two or more autonomous, often dissimilar, functions using a single polypeptide chain. They have been increasingly reported on the surface of both prokaryotic and eukaryotic organisms and shown to interact with a variety of host ligands. In some organisms moonlighting proteins perform virulence-related functions, and they may play a role in the pathogenesis of N. meningitidis. Fructose-1,6- bisphosphate aldolase (FBA) was previously shown to be surface-exposed in meningococci and involved in adhesion to host cells. In this study, FBA was shown to be present on the surface of both pathogenic and commensal neisseriae, and surface localization and anchoring was demonstrated to be independent of aldolase activity. Importantly, meningococcal FBA was found to bind to human glu- plasminogen in a dose-dependent manner. Site-directed mutagenesis demonstrated that the C-terminal lysine residue of FBA was required for this interaction, whereas # subterminal lysine residues were not involved.